2014
DOI: 10.3389/fnins.2014.00219
|View full text |Cite
|
Sign up to set email alerts
|

A review on auditory space adaptations to altered head-related cues

Abstract: In this article we present a review of current literature on adaptations to altered head-related auditory localization cues. Localization cues can be altered through ear blocks, ear molds, electronic hearing devices, and altered head-related transfer functions (HRTFs). Three main methods have been used to induce auditory space adaptation: sound exposure, training with feedback, and explicit training. Adaptations induced by training, rather than exposure, are consistently faster. Studies on localization with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 73 publications
0
56
0
Order By: Relevance
“…It has been demonstrated that listeners can adapt to artificially produced changes of the spatial cues responsible for correct sound source location (for a review, see Mendonça, 2014). This plasticity in spatial hearing has been demonstrated both in the horizontal and vertical plane for various manipulations of the localization cues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that listeners can adapt to artificially produced changes of the spatial cues responsible for correct sound source location (for a review, see Mendonça, 2014). This plasticity in spatial hearing has been demonstrated both in the horizontal and vertical plane for various manipulations of the localization cues.…”
Section: Discussionmentioning
confidence: 99%
“…This notion emerged, for instance, from studies that examined re-learning of sound-space correspondences when auditory cues were temporarily altered using monaural ear-plugs (Rabini et al, 2019;Strelninkov et al, 2011;Trapeau & Schönwiesner, 2015), ear molds (Van Wanrooij & Van Opstal, 2005) or non-individualised HRTFs (Head-Related Transfer Functions; Honda, Shibata, Gyoba, Saitou, Iwaya & Suzuki, 2007;Parseihian & Katz, 2012;Steadman, Kim, Lestang, Goodman & Picinali, 2019). In these simulated altered-listening conditions, multisensory training procedures proved effective for re-learning sound-space correspondences (for reviews see: Carlile, 2014;Keating & King, 2015;Knudsen & Knudsen, 1985;Mendonça, 2014;Irving & Moore, 2011). For instance, Strelnikov and colleagues (2011) studied the effects of audio-visual vs. auditory-only training on sound localisation in monaurally-plugged adults.…”
Section: Introductionmentioning
confidence: 99%
“…While there is consensus that rapid adaptation is possible in the auditory system [14,15,16,8,17,18,19], so far, studies have reported different results on the reweighting of the different monaural and binaural localization cues and prior information sources to estimate a sound's direction [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%